Estudio Comparativo de los personajes de “La oveja negra y demás fábulas” de Augusto Monterroso y de “Historias de cronopios y de famas” de Julio Cortázar - Maldonado Rodríguez, Whitney Walkiria (2024)
This research aimed to establish the relationship among the characters in the works “La oveja negra y demás fábulas” by Augusto Monterroso and “Historias de cronopios y de famas” by Julio Cortázar. The design was qualitative, involving a comparative study of two literary works through bibliographic, exploratory, descriptive, and correlational research. The study, of a longitudinal nature, used the entirety of the micro-stories contained in the analyzed works as the unit of analysis. The results present a proposal for character characterization, psychological analysis, and finally, a comparative analysis of the works considering archetypes, motivations, conflicts, and the historical context of the works. It is concluded that evaluating the impact of characters in the selected micro-stories by Monterroso and Cortázar highlights how the ingenious and sometimes surreal interaction of characters propels the plots, adding layers of meaning and challenging narrative expectations. Therefore, it is recommended to include an analysis of the critical reception of the works at different times and contexts. This could provide valuable information on how they have been received and perceived over the decades.